Polymerase chain reaction for screening clinical isolates of corynebacteria for the production of diphtheria toxin. Issue 4 (April 1994) - Pallen, M J; Hay, A J; Puckey, L H; Efstratiou, A
Abstract : AIMS--To assess the performance of the polymerase chain reaction (PCR) when used to screen rapidly large numbers of corynebacteria for toxin production; and to determine the incidence of false positive PCR results with non-toxigenic Corynebacterium diphtheriae isolates. METHODS--Eighty seven recent British isolates of corynebacteria were assayed by PCR. All isolates were assayed from both blood and tellurite agar within a five day period. Thirty three non-toxigenic isolates of C diphtheriae from six countries were also tested by PCR and by the Elek immunodiffusion assay. RESULTS--There was complete concordance between the results of PCR and traditional methods on the recent British isolates, with one exception: an Elek positive "C ulcerans" isolate, which was PCR positive from tellurite but not from blood agar. One of the thirty three (3%) non-toxigenic isolates of C diphtheriae was PCR positive. CONCLUSIONS--These results suggest that PCR compares favourably with traditional methods for the detection of toxigenic corynebacteria and that it represents a powerful new tool in the diagnosis of an old disease.